Spontaneous spinal epidural haematoma due to arteriovenous malformation in a child - Cabral, António Jorge (BMJ Publishing Group, 2011)
Spontaneous spinal epidural haematoma (SSEH) is a rare clinical entity, especially in infants, in whom only a few cases have been reported. In a paediatric emergency setting, SSEH should be considered as part of the differential diagnosis for acute extremity weakness and paraesthesia. Epidural vascular malformations are often suspected in these cases but have rarely been demonstrated. The authors report herein a case of SSEH in a 9-year-old boy arising from an epidural vascular malformation. He initially presented with sudden intense cervicodorsal pain followed by hypotonic lower extremities and progressive motor weakness, with no sensory change. The MRI showed an acute extradural haematoma extending from C7 to T4 with compression of the spinal cord. After submission to decompression surgery, he presented full recovery in 1 month. The histopathological analysis revealed a vascular malformation.